2021
DOI: 10.1186/s12904-021-00852-w
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity and acceptability of the traditional Chinese version of the carer support needs assessment tool in Hong Kong palliative care settings

Abstract: Background Among the few existing needs assessment tools for family carers, the 14-item Carer Support Needs Assessment Tool (CSNAT) is the only brief and holistic needs screening tool designed for everyday use in palliative care practices. The aim of this study was to evaluate the reliability, validity, and acceptability of the traditional Chinese version of the CSNAT in palliative care settings in Hong Kong. Methods This adopted a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Local research has also reported this similar finding, indicating that caregivers have unmet support needs in personal care, practical household support, providing personal care, financial, legal and work issues, and equipment to care for patients. 30,31 The current findings suggest that there is an urgent need to ease caregiver burden by designing services to address their unmet needs.…”
Section: Discussionmentioning
confidence: 88%
“…Local research has also reported this similar finding, indicating that caregivers have unmet support needs in personal care, practical household support, providing personal care, financial, legal and work issues, and equipment to care for patients. 30,31 The current findings suggest that there is an urgent need to ease caregiver burden by designing services to address their unmet needs.…”
Section: Discussionmentioning
confidence: 88%
“…The participant profile was previously reported 19 . 125 family caregivers participated in this study and the response rate was 74.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional Chinese version of the 14‐item Carer Support Needs Assessment Tool (CSNAT) assesses participants' unmet support needs 9,19 . As the CSNAT tool was constructed as a screening tool, rather than a scale, each item represents a core support domain for future support.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations